Experimental research of impact on psychological state for adolescents with high-intensity interval training intervention - Li, Yu-Tong; Zhou, Yang (Frontiers in Psychology, 2025)
IntroductionRising social pressures have exacerbated adolescent mental health challenges, evidenced by increasing prevalence of anxiety, depression, and related disorders. High-intensity interval training (HIIT), characterized by short bursts of intense exercise interspersed with recovery periods, has emerged as a time-efficient intervention for psychological well-being. This study quantitatively evaluated the efficacy of HIIT in improving adolescent mental health using the Multidimensional Scale of Adolescent Psychological State (MSAPS), which assesses seven domains: self-esteem, energy, tension, anger, depression, fatigue, and confusion.MethodsA randomized controlled trial was conducted with 60 adolescents (aged 14–18 years) from Handan City Sports School. Participants were equally divided into an experimental group (HIIT intervention) and a control group (moderate-intensity continuous training). The HIIT protocol involved heart rate zones of 172 ±10 bpm, while the control group trained at 132 ± 10 bpm. Both interventions lasted 8 weeks. Pre- and post-intervention psychological assessments were performed using MSAPS, with statistical analyses employing paired t-tests for within-group comparisons and ANCOVA for between-group effects.ResultsThe HIIT group demonstrated significant reductions in negative affect: tension (Δ = 2.1, p = 0.002), depression (Δ = 1.5, p = 0.008), and anger (Δ = 1.9, p = 0.001), alongside a substantial increase in self-esteem (Δ = 1.7, p = 0.004). The control group showed modest improvements in tension (Δ = 0.9, p = 0.03) and depression (Δ = 0.6, p = 0.04), but effects were weaker and non-significant for anger and self-esteem. Between-group analyses revealed HIIT’s superiority in tension (Δ = 1.8, p = 0.00) and depression (Δ = 0.8, p = 0.017) compared to continuous training.DiscussionHIIT’s dual mechanism—stimulating endorphin/dopamine release and enhancing physical efficacy—likely underpins its psychological benefits. The findings support HIIT as a viable school-based intervention for mitigating anxiety/depression and boosting self-esteem in adolescents. These results provide empirical groundwork for integrating HIIT into physical education curricula and mental health promotion strategies, offering a practical alternative to traditional exercise modalities.